2004
DOI: 10.1007/s10194-004-0103-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional imaging of subcortical nociceptive structures in response to treatment of chronic daily headache

Abstract: The objective was to provide objective imaging evidence of functional changes in brainstem structures involved in chronic daily headache (CDH). Over time, episodic migraine (EM) patients may develop CDH known as transformed migraine (TM). Using analysis of transverse relaxation rates, R2, R2* and R2' (R2* values are reflective of blood oxygen level dependence; R2' is a measure of non-heme iron in tissues) we have reported activation (hyperoxia) of red nucleus (RN) and substantia nigra (SN) (decreased R2* and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Some preliminary work along these lines has already been reported: brain stem changes in PCM appear to resolve after effective treatment. 25 A complete picture of brainstem-cortex relationships in PCM, over the evolution of the disorder, should be the goal of investigators in this area: we feel that the goal is attainable with the appropriate techniques of both neuroimaging and TMS-based functional studies as reported here.…”
Section: Discussionmentioning
confidence: 90%
“…Some preliminary work along these lines has already been reported: brain stem changes in PCM appear to resolve after effective treatment. 25 A complete picture of brainstem-cortex relationships in PCM, over the evolution of the disorder, should be the goal of investigators in this area: we feel that the goal is attainable with the appropriate techniques of both neuroimaging and TMS-based functional studies as reported here.…”
Section: Discussionmentioning
confidence: 90%
“…Some preliminary work along these lines has already been reported: brain stem changes in CM appear to resolve after effective treatment. 36 A complete picture of brainstem-cortex relationships in CM, over the evolution of the disorder, should be the goal of investigators in this area: we feel that the goal is attainable with the appropriate techniques of both neuroimaging and TMS-based functional studies as reported here.…”
Section: Commentsmentioning
confidence: 89%
“…Recent pathophysiological theories suggest that migraine may be a disorder of the neurovegetative and nociceptive brainstem, and that local imbalances in the activity of hypothalamic and brainstem circuitry could be implied in the initiation and termination of migraine attacks (May 2017 ). Although the involvement of RN in such circuitry in the human brain is yet to be clarified, some fMRI studies report intense activation and hyperoxia of bilateral RN during both spontaneous and visually-triggered migraine (Welch et al 1998 ; Cao et al 2002 ; Aurora et al 2004 ). More recently, resting-state fMRI has been used to study functional connectivity of brainstem structures in migraineurs, reporting altered functional connectivity between RN, parietal lobe and cerebellum (Huang et al 2019 ).…”
Section: From Anatomy To Clinic: Rn In Neurological Diseasesmentioning
confidence: 99%